Drifting in a free-flowing river: Distribution of fish eggs and larvae in a small tributary of a Neotropical reservoir - Azevedo-Santos, Valter M. [UNESP]; Daga, Vanessa S.; Pelicice, Fernando M.; Henry, Raoul [UNESP] (Revista Biota Neotropica, 2021)
We investigated spatial and temporal variations in the distribution of fish eggs and larvae in the Guarei River, a free-flowing tributary located in the upper section of the Jurumirim Reservoir, Paranapanema River, Brazil. Fish eggs and larvae were sampled similar to fortnightly from November 2017 to March 2018 (Cycle 1), and from November 2018 to March 2019 (Cycle 2), at three sites distributed along the entire course of the Guarei River. We collected 859 fish eggs and 1,340 larvae, comprising 19 taxa. We found reproductive activity of several fish species in the Guarei River, including long-distance migrants. However, there was no spatial differences in the assemblage structure and densities of fish eggs and larvae along the channel of Guarei River. We recorded temporal differences in larvae density only in Cycle 2. The consistent capture of fish eggs and larvae in two reproductive cycles is strong evidence that this river is a spawning site for a variety of fish species. Thus, we recommend maintaining its natural flow regime.
Keywords: Fish reproduction; Ichthyoplankton; Jurumirim Reservoir; Migratory fish; Prochilodus lineatus